Impact of the global financial crisis and its implications for the Zambian banking sector: an econometric study - Sichula, Mwembe (Research of GSB, 2019)
The research examines how the banking sector in Zambia faired in the wake of the global financial crisis, and the ensuing global recession that followed. Even prior to the crisis, weaknesses within the Zambian Banking sector were already identified by a World Bank/IMF financial sector assessment. The research therefore aims to gain a better understanding of the potential destabilizing factors to the Zambia Banking sector, and provide key players (Policymakers, Regulators and Banks) with knowledge on how best to manage and overcome these adverse effects, in times of a financial crisis. A Vector Error Correction Model (VECM) is estimated using commonly identified macroeconomic and banking sector indicators from selected Anglophonic African countries that were affected by the crisis at the time. The selected variables include, Return on Assets (ROA); Non-Performing Loans (NPL); Foreign Assets (FA); Interbank Lending Rate (IBLR); Liquidity (LQD); Credit to Private Sector (PRV); Foreign Exchange Rate (FOREX); Inflation (INFL); Copper Price (CU); and a ‘dummy’ variable (CRISIS). The direction of causality between the variables is further established using the VAR Granger Causality Test. Results of the model suggests that although the CRISIS was found to cause the ROA, it had no significant effect on its outcome, implying that overall the crisis had very little effect on the Zambian banking sector’s profitability. It was the liquidity (LQD) variable instead which was found to have a significant effect on the ROA. In times of a financial crisis, it is therefore recommended that policy makers and regulators apply more stringent regulatory and monetary policy instruments. This would counter the adverse effects on the liquidity and profitability of the Banking sector, and thus ensure its stability.